Rozner, Sarah (audio interview #1 of 20) - Rozner, Sarah (b. 1892 - d. 12/?/1980); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - This is the tenth interview with Sarah Rozner conducted in her home. This interview has a problem with the audio quality when Rozner speaks too closely into the microphone. TOPICS - 1938 move to Los Angeles; activities in Los Angeles; factionalism in ACWA: work as a union organizer; conditions in the Los Angeles job market and in the union; ACWA shift to New Dealism;ideological shift in the ACWA; conditions in the union in Los Angeles; role as chairwoman at Louart,1946; treatment of women in the union; 8/7/1973